Magnetohydrodynamic Casson Hybrid Nanofluid Dynamics in Circulating Blood Considering Thermal Radiation and Chemical Reaction - Durga Priyadarsini, G.; Asma Kauser, Syeda; Hari Krishna, Y.; Nageswara Rao, T.; Venkatta Ramana Reddy, Gurrampati (East European Journal of Physics, 2025)
The purpose of this work is to investigate the relevance of thermal radiation and chemical reaction in the thermal and radiative analysis of hybrid Casson nanofluid dynamics. The physical model was based on the mixture of Gold and Silver hybrid nanoparticles (HN) which are suspended in a blood past a stretchable sheet. The dynamics of fluid past a stretchable sheet is a notable analysis for thermal and momentum boundary layers. It finds applications in various technological fields and in industries. The model equations were investigated using a system of partial differential equations (PDEs). Acceptable transformation was used to convert these PDEs into total differential equations (ODEs). Later, the system of equations was solved using the Runge-Kutta algorithm along with shooting. The analysis described in this paper explained that hybrid nanoparticles have high performance in radiative and thermal processes when compared with nanofluid. The fluid's velocity was observed to be repelled by an increasing magnetic value because of the Lorentz force. A comparison with previous work showed close agreement.